Inhibition of cell wall pectin metabolism by plasma activated water (PAW) to maintain firmness and quality of postharvest blueberry - Cheng, Jun-Hu (Plant physiology and biochemistry : PPB, 2023)
Copyright © 2023 Elsevier Masson SAS. All rights reserved.